Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(3x-5\right)\left(9x^2+15x+25\right)\)
\(=\left(3x\right)^3-5^3\)
\(=27x^3-125\)
b) \(\left(2x+7\right)\left(x^2-14x+49\right)-2x\left(2x-1\right)\left(2x+1\right)\)
\(=2x^3-28x^2+98x+7x^2-98x+343-2x\left(4x^2-1\right)\)
\(=2x^3-28x^2+7x^2+343-8x^3+2x\)
\(=-6x^3-21x^2+343+2x\)
c) \(\left(4x-7\right)\left(16x^2+28x+49\right)\left(3x+1\right)\left(9x^2-3x+1\right)-9x\left(3x^2-1\right)\)
\(=\left(64x^3-343\right)\left(3x+1\right)\left(9x^2-3x+1\right)-27x^3+9x\)
\(=\left(6x^3-343\right)\left(27x^3+1\right)-27x^3+9x\)
\(=1728x^6+64x^3-9261x^3-343-27x^3+9x\)
\(=1728x^6-9224x^3-343+9x\)
b: \(\Leftrightarrow\dfrac{7x+10}{x+1}\left(x^2-x-2-2x^2+3x+5\right)=0\)
\(\Leftrightarrow\left(7x+10\right)\left(-x^2+2x+3\right)=0\)
\(\Leftrightarrow\left(7x+10\right)\left(x^2-2x-3\right)=0\)
=>(7x+10)(x-3)=0
hay \(x\in\left\{-\dfrac{10}{7};3\right\}\)
d: \(\Leftrightarrow\dfrac{13}{2x^2+7x-6x-21}+\dfrac{1}{2x+7}-\dfrac{6}{\left(x-3\right)\left(x+3\right)}=0\)
\(\Leftrightarrow\dfrac{13}{\left(2x+7\right)\left(x-3\right)}+\dfrac{1}{\left(2x+7\right)}-\dfrac{6}{\left(x-3\right)\left(x+3\right)}=0\)
\(\Leftrightarrow26x+91+x^2-9-12x-14=0\)
\(\Leftrightarrow x^2+14x+68=0\)
hay \(x\in\varnothing\)
a) \(5x\left(3x-7\right)-15x\left(x-1\right)=3\)
\(\Rightarrow15x^2-35x-15x^2+15x=3\)
\(\Rightarrow-20x=3\)
\(\Rightarrow x=-\dfrac{3}{20}\)
b) \(\left(4x+2\right)\left(6x-3\right)-\left(8x+5\right)\left(3x-4\right)=2\)
\(\Rightarrow24x^2+12x-12x-6-24x^2-15x+24x+20=2\)
\(\Rightarrow9x+14=2\)
\(\Rightarrow9x=-12\)
\(\Rightarrow x=-\dfrac{4}{3}\)
c) \(7x^2-21x=0\)
\(\Rightarrow7x\left(x-3\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}7x=0\\x-3=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=3\end{matrix}\right.\)
d) \(9x^2-6x+1=0\)
\(\Rightarrow\left(3x\right)^2-2.3x+1=0\)
\(\Rightarrow\left(3x-1\right)^2=0\)
\(\Rightarrow3x-1=0\)
\(\Rightarrow3x=1\)
\(\Rightarrow x=\dfrac{1}{3}\)
e) \(16x^2-49=0\)
\(\Rightarrow\left(4x\right)^2-7^2=0\)
\(\Rightarrow\left(4x-7\right)\left(4x+7\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}4x-7=0\\4x+7=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}4x=7\\4x=-7\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\dfrac{7}{4}\\x=-\dfrac{7}{4}\end{matrix}\right.\)
f) \(5x^3-20x=0\)
\(\Rightarrow5x\left(x^2-4\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}5x=0\\x^2-4=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=5\\x^2=4\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5\\x=2\\x=-2\end{matrix}\right.\)
Ta có: \(\left(x+7\right)\left(3x-1\right)=49-x^2\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)=\left(7-x\right)\left(7+x\right)\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)-\left(7-x\right)\left(x+7\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1-7+x\right)=0\)
\(\Leftrightarrow\left(x+7\right)\left(4x-8\right)=0\)
\(\Leftrightarrow\left(x+7\right)\cdot4\cdot\left(x-2\right)=0\)
Vì 2≠0
nên \(\left[{}\begin{matrix}x+7=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-7\\x=2\end{matrix}\right.\)
Vậy: x∈{-7;2}
\(\left(x+7\right)\left(3x-1\right)=49-x^2\)
\(\Leftrightarrow\left(x+7\right)\left(3x-1\right)=\left(x+7\right)\left(7-x\right)\)
\(\Leftrightarrow3x-1=7-x\)
\(\Leftrightarrow4x=8\Leftrightarrow x=2\)
Vậy...